Is It Worth Using Gamification on Software Testing Education?: An Experience Report - de Jesus, Gabriela Martins; Paschoal, Leo Natan; Ferrari, Fabiano Cutigi; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Context: Testing is essential to improve the quality of software products. Despite that, it is not a subject that students are motivated to learn. Gamification is a promising way to address issues in software testing education; it is used to insert game elements in educational contexts aiming to increase students' motivation and performance. Objective: Reporting on results of an experimental study designed to assess the impact of gamification on software testing education. Method: We carried out the experimental sessions with undergraduate students from three Brazilian institutions. They have been taught basic testing concepts and functional testing. Moreover, the experimental group used a gamified platform that included 10 game elements to increase students' motivation and performance, attract their attention, and instigate their participation, collaboration, and competitiveness. Results: The experimental group was more motivated than the control group. Regarding performance, the experimental group had an equivalent performance compared to the control group in the pre- and post- tests. However, we observed a trend for the control group to reach a higher performance, as the results from the quiz activities showed significant difference. Conclusion: Although several studies concluded that gamification has the potential to lead to positive outcomes, we reached both positive and negative results. So that, we present our findings and answer whether, in our point of view, it is worth using gamification on software testing education.